32 Influence of Sleep Apnoea on Biventricular Pacing, Heart Rate Trend and Tachyarrhythmia's in Heart Failure Patients who have undergone Cardiac Resynchronisation Therapy. (6th June 2015) - Swamydass, Daniel; Gilmore, Mark; Barry, James; Edmunds, Eiry; Anderson, Mark; Warren, Claire; Lewis, Keir
Abstract : Introduction: Sleep apnoea syndrome (SAS) has been reported in 40–60% of people with heart failure (HF) 1 with varying reports as to whether this is predominantly central or obstructive. Undiagnosed intermittent hypoxia during sleep increases sympathetic activation and endothelial dysfunction so may worsen cardiac outcomes. SAS also prevents the normal drop in heart rate that accompanies the onset of sleep and coupled with reflex increases in central sympathetic outflow could lead to the development of recurrent nocturnal ischaemia and arrhythmias. 2 We compared average heart rate, percentage of Biventricular pacing and logged tachyarrhythmia's in those with and without recently diagnosed SAS in a specific cohort of HF patients who underwent cardiac resynchronisation therapy (CRT). Method: Prospective, cross-sectional study. 37 Consecutive HF patients, 30 males, mean (SD) age= 69.8 (8.4) yrs, BMI 29.3 (8.7) kg/m 2, and mean LVEF 25 (7)% – who were referred to a UK tertiary cardiac centre for CRT according to National Guidelines. They underwent baseline limited channel sleep studies (Apnea Link TM ResMed, Abingdon, UK) immediately prior to CRT. All patients were deemed on optimal medication at the discretion of a cardiologist. None had known SAS. An apnoea hyopnea index (AHI) >15 events per hour was deemed a positive result for treatable SAS according to UK guidelines. Average heart rate, percentage of biventricular pacing and logged tachyarrhythmias were obtained from six weeks post CRT follow up. Results: 20 from 37 (54%) had an AHI >15 events per hour. All 20 patients had predominantly obstructive sleep apnoea, 5 of these 17 patients had some central sleep apnoea, but this was still less than their obstructive episodes. None had predominantly central sleep apnoea. Conclusion: There is a high prevalence (54%) of significant SAS in the group of heart failure patients referred for CRT. Unlike other studies we found a relatively low prevalence of central sleep apnoea. There was no difference in average heart rate and percent of biventricular pacing in those with and without SAS. However there is increased incidence of tachyarrhythmias in those with SAS and this might be explained by recurrent hypoxia and increased sympathetic activity in sleep apnoea patients. References: Eur Resp J. 2007;29(6):1201-5 Circulation 2003;107:1671-8